In Situ Atomic Force Microscopy of the Reconfiguration of On‐Surface Self‐Assembled DNA‐Nanoparticle Superlattices. (4th January 2019) - Shekhirev, Mikhail; Sutter, Eli; Sutter, Peter
Abstract: The ability to dynamically reconfigure superlattices in response to external stimuli is an intriguing prospect for programmable DNA‐guided nanoparticle (NP) assemblies, which promises the realization of "smart" materials with dynamically adjustable interparticle spacing and real‐time tunable properties. Existing in situ probes of reconfiguration processes have been limited mostly to reciprocal space methods, which can follow larger ordered ensembles but do not provide access to real‐space pathways and dynamics. Here, in situ atomic force microscopy is used to investigate DNA‐linked NP assemblies and their response to external stimuli, specifically the contraction and expansion of on‐surface self‐assembled monolayer superlattices upon reversible DNA condensation induced by ethanol. In situ microscopy allows observation and quantification of key processes in solution, e.g., lattice parameter changes, defects, and monomer displacements in small groups of NPs. The analysis of imaging data uncovers important boundary conditions due to DNA bonding of NP superlattices to a substrate. Tension in the NP–substrate DNA bonds, which can elastically extend, break, and re‐form during contraction/expansion cycles, counteracts the changes in lattice parameter and causes hysteresis in the response of the system. The results provide insight into the behavior of supported DNA‐linked NP superlattices and establish a foundation for designing and probing tunable nanocrystal‐based materials in solution. Abstract : The reconfiguration of DNA‐linked substrate‐supported nanoparticle assemblies in response to ethanol added to the aqueous solution is studied using in situ atomic force microscopy. In situ imaging directly shows the changes to the monolayer superlattice during ethanol‐induced contraction and expansion. A statistical analysis of the interparticle spacings reveals hysteresis in the lattice parameter due to the nanoparticle–substrate DNA bonding.